OBJECT OF ISLAMIC EDUCATION THEORY BASED ON COMMUNITY DEVELOPMENT - Abdul Hayyi; Zamroni Zamroni; Yosi Huzna Nidia Ningrum Ningrum (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to examine the object of Islamic educational theory based on a community approach by tracing the historical and conceptual roots of critical education, as well as its relevance in contemporary social, political, and cultural contexts. Islamic education from a critical perspective is understood not only as a process of knowledge transfer, but also as a means of liberation and human empowerment from various forms of structural, ideological, and cultural oppression. This study uses a descriptive qualitative approach with a literature study method, which examines relevant national journals indexed by Sinta 2 and international articles (2020–2025). The analysis was carried out using the interactive model of Miles and Huberman, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that critical education in Islam has a strong theological basis, rooted in the values of amar ma'ruf nahi munkar and the principle of tahrīr al-insān (human liberation). Islamic education is understood as a process of spiritual and social emancipation that fosters reflective awareness, builds moderation, and strengthens the cultural identity of the community. Furthermore, Islamic education serves as a political product, a means of cultural resistance, and a preserver of just and civilized local values. Thus, the theory of community-based Islamic education integrates spirituality, rationality, and social awareness to shape individuals who are faithful, knowledgeable, and civilized.